A construção do si mesmo na adolescência: estudo realizado em uma perspectiva winnicottiana - Morelli, Marcia Briza (2013)
The objective of this research is to develop a study on the construction of self in adolescence from Winnicott's theory of development and a reflection on the contact with adolescents in therapy. Human development is described from conception to early adulthood, with emphasis on the constitution of self from an inherited potential, the relationship with the environment and the integration of essential aspects of human life such as time, space, body and relationship with others. Two clinical cases are presented